Rethinking English Classroom Practices in the Post-COVID Bangladesh: Making a Case for Blended-learning - Hossen, Mohammad Sajjad (Journal of NELTA, 2023)
The COVID-19 pandemic caused large-scale disruption to education worldwide and forced educational institutions to switch to online education. During this pandemic, Bangladeshi educational institutions also transitioned to online teaching. While most teachers and students felt immensely challenged by this new mode of education because of a lack of training and infrastructural limitations, some English language teachers were found to exploit this opportunity to teach online using accessible technologies. The teachers who successfully integrated technology in the classroom recommended continuing online education in the post-COVID period because of the benefi ts this mode of education off ers. However, they did not suggest online education as a substitute for in-person education. This systematic review critically examined the literature that explored Bangladeshi teachers’ and students’ experiences of COVID-19 online education to understand if online education offers any solutions to the challenges that negatively aff ect the country’s secondary-level English education. Based on the meta-analysis of data, this review paper makes a case for blended learning for English language classrooms in Bangladesh, as research on blended learning shows that this dual-mode education can address the issues of space, time, and reach that negatively impact the country’s English language education. More importantly, the blended approach can reduce inequities that characterize the current English language classrooms in the country and can, consequently, increase inclusion. Accordingly, drawing on global and local scholarship, this paper sheds light on various features of blended education.